The effects of covid-19 outbreak on financial markets - Ismail Çelik; Tayfun Yilmaz; Süleyman Emir; Ahmet Furkan Sak (Financial Studies, 2020)
The purpose of this paper is to measure the risks posed by the COVID-19 outbreak on financial market indicators, which caused uncertainty and fear all over the world. In the paper, the Fourier KPSS unit root test, which helps to measure structural breaks more precisely by means of the Fourier transformations in time series, the Fourier-SHIN Cointegration Test to determine long-term relationships between time series, and the Fourier Granger Causality Test to determine causality relationships are used. As a result of these tests applied on the daily price series between 31.12.2019 and 01.05.2020, it has been found that in the long term, the COVID-19 outbreak has a significant effect on stock markets, crude oil representing oil markets, and fear index; but no significant effect on Bitcoin which represents money markets. In the short term, it is concluded that COVID-19 has had a significant effect on stock markets, crude oil, fear index, and Bitcoin.
Keywords: C58; G15; 330; COVID-19; Fourier Transformations; Causality; Cointegration; Financial Markets